Die kairos van die New Age: "n Kultuurhistoriese skets - Schulze, L.F. (Hervormde teologiese studies, 1992)
The kairos of the New Age movement: A cultural historical outline The precursor of the New Age movement was theosophy. With the foundation of the Theosophical Society (1875) certain basic ideas inherent in Western thought were restated in a new context. In the cultural climate of the 1880s notions of a subjective, anti-positivist stance, tending towards mysticism, were common, especially among the symbolists. In this respect the symbolists were reflecting a cultural and intellectual climate that facilitated the emergence of theosophy. In our century two currents have led toward the New Age movement: firstly, the persisting influence of theosophists especially that of Bailey and, secondly, the intensified statement of symbolist ideas and ideals.